Ni2P Nanoalloy as an Air‐Stable and Versatile Hydrogenation Catalyst in Water: P‐Alloying Strategy for Designing Smart Catalysts. Issue 13 (3rd February 2021) - Fujita, Shu; Yamaguchi, Sho; Yamasaki, Jun; Nakajima, Kiyotaka; Yamazoe, Seiji; Mizugaki, Tomoo; Mitsudome, Takato
Abstract: Non‐noble metal‐based hydrogenation catalysts have limited practical applications because they exhibit low activity, require harsh reaction conditions, and are unstable in air. To overcome these limitations, herein we propose the alloying of non‐noble metal nanoparticles with phosphorus as a promising strategy for developing smart catalysts that exhibit both excellent activity and air stability. We synthesized a novel nickel phosphide nanoalloy (nano‐Ni2 P) with coordinatively unsaturated Ni active sites. Unlike conventional air‐unstable non‐noble metal catalysts, nano‐Ni2 P retained its metallic nature in air, and exhibited a high activity for the hydrogenation of various substrates with polar functional groups, such as aldehydes, ketones, nitriles, and nitroarenes to the desired products in excellent yields in water. Furthermore, the used nano‐Ni2 P catalyst was easy to handle in air and could be reused without pretreatment, providing a simple and clean catalyst system for general hydrogenation reactions. Abstract : Air‐stable non‐noble metal nanoparticles : A novel nickel phosphide nanoalloy (nano‐Ni2 P) retained its metallic nature in air and exhibited a high activity for the hydrogenation of carbonyls, nitriles, and nitroarenes in water. The used nano‐Ni2 P could be easily handled and reused without pretreatment, providing a simple and clean catalyst system for general hydrogenation reactions.